2005
DOI: 10.1590/s1806-83242005000300011
|View full text |Cite
|
Sign up to set email alerts
|

DNA extraction from human saliva deposited on skin and its use in forensic identification procedures

Abstract: Saliva is usually deposited in bite marks found in many homicides, assault and other criminal cases. In the present study, saliva obtained from volunteers was deposited on skin and recovered for DNA extraction and typing in order to evaluate its usefulness for practical case investigation and discuss the contribution of forensic dentistry to saliva DNA typing. Twenty saliva samples were colleted from different donors and used as suspects' samples. Five of these samples were randomly selected and deposited (250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 19 publications
(30 reference statements)
2
20
0
3
Order By: Relevance
“…DNA from 1.5ml of each saliva specimen was centrifuged and the DNA was isolated from the cell pellet using the phenol-chloroform method described by Anzai-Kanto et al 16 . Two microliters of DNA were used in each PCR reaction.…”
Section: Dna Extraction From Saliva Primers and Polymerase Chain Reamentioning
confidence: 99%
“…DNA from 1.5ml of each saliva specimen was centrifuged and the DNA was isolated from the cell pellet using the phenol-chloroform method described by Anzai-Kanto et al 16 . Two microliters of DNA were used in each PCR reaction.…”
Section: Dna Extraction From Saliva Primers and Polymerase Chain Reamentioning
confidence: 99%
“…The amount of saliva deposited on the skin is usually very small in bite marks; in addition, environmental factors, such as heat, bacteria, moisture, and mold, can render the DNA unusable (Wick, 2000). Partial profiles were obtained even under controlled experimental conditions, wherein the saliva was placed on the skin of volunteers (Anzai-Kanto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies have shown that the double-swab technique allowed for the identification of pure DNA profiles (Sweet et al, 1997a,b;Anzai-Kanto et al, 2005). However, the use of the single swab technique may be more appropriate in actual cases, wherein the skin surface is disrupted and the sample might be contaminated with the DNA of the victim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In modern days with development of technology application of the knowledge of dental and paradental knowledge helps in solving many legal issues in civil and criminal matters [4][5][6].…”
Section: Opinionmentioning
confidence: 99%